2007
DOI: 10.1093/toxsci/kfm220
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium-Induced Germline Apoptosis in Caenorhabditis elegans: The Roles of HUS1, p53, and MAPK Signaling Pathways

Abstract: The transition metal cadmium (Cd) has been shown to induce apoptosis in a variety of cell lines and tissues. Caspase activation of the tumor suppressor gene p53 and mitogen-activated protein kinase (MAPK) signaling cascades have been reported to be involved in Cd-induced apoptosis. However, the underlying pathways of Cd-induced apoptosis have not been clearly elucidated in the in vivo systems, primarily for the lack of appropriate animal models. The nematode Caenorhabditis elegans has been shown to be a good m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 38 publications
5
24
1
Order By: Relevance
“…However, Ni-induced germline apoptosis is decreased in mutant homologs of the JNK ( jkk-1 , mek-1 , jnk-1 , and mkk-4 loss-of-function strains) and p38 MAPK ( nsy-1 , sek-1 , pmk-1 , and pmk-3 loss-of-function strains) signaling cascades, indicating the significance of these two pathways in Ni-induced apoptosis in C. elegans (Kezhou et al, 2010). Similarly, Cd exposure in C. elegans also induces germline apoptosis in a manner dependent upon the JNK and p38 MAPK pathways, as indicated by the blockage of apoptosis in Cd-exposed JNK and p38 MAPK pathway homolog knockouts (except in loss-of-function pmk-3 mutants; Wang et al, 2008). Also analogous to Ni-induced apoptotic pathways, both cep-1 and hus-1 play non-essential roles in germline apoptosis in warms exposed to 50 μM Cd (Wang et al, 2008), suggesting the lack of involvement of the DNA damage response in mediating metal-induced apoptosis in C. elegans .…”
Section: Metal-induced Apoptosismentioning
confidence: 99%
“…However, Ni-induced germline apoptosis is decreased in mutant homologs of the JNK ( jkk-1 , mek-1 , jnk-1 , and mkk-4 loss-of-function strains) and p38 MAPK ( nsy-1 , sek-1 , pmk-1 , and pmk-3 loss-of-function strains) signaling cascades, indicating the significance of these two pathways in Ni-induced apoptosis in C. elegans (Kezhou et al, 2010). Similarly, Cd exposure in C. elegans also induces germline apoptosis in a manner dependent upon the JNK and p38 MAPK pathways, as indicated by the blockage of apoptosis in Cd-exposed JNK and p38 MAPK pathway homolog knockouts (except in loss-of-function pmk-3 mutants; Wang et al, 2008). Also analogous to Ni-induced apoptotic pathways, both cep-1 and hus-1 play non-essential roles in germline apoptosis in warms exposed to 50 μM Cd (Wang et al, 2008), suggesting the lack of involvement of the DNA damage response in mediating metal-induced apoptosis in C. elegans .…”
Section: Metal-induced Apoptosismentioning
confidence: 99%
“…In 2002, Kim et al (2002) demonstrated that NSY-1 and its downstream MAPK kinase (MAP2K) SEK-1 and MAPK PMK-1 were indispensable for the immune response to various bacterial infections, including Pseudomonas aeruginosa. In addition, nsy-1 mutant animals have been reported to show sensitivity to gram-positive bacteria Staphylococcus aureus with a defect in germline apoptosis (Sifri et al 2003), sensitivity to oxidative stress (Kondo et al 2005), resistance to germline apoptosis upon arsenite or cadmium stimulation Wang et al 2008) and a defect in egg laying (Shivers et al 2009). These phenotypes of nsy-1 mutant animals strongly suggest that NSY-1 plays important roles in stress responses in C. elegans.…”
mentioning
confidence: 99%
“…Blackwell et al (2015) showed that sodium arsenite or other oxidative stressors activated p38 kinase through phosphorylation process in C. elegans. On the other hand, a study by Wang et al (2008) reported that cadmium-induced germline apoptosis of C. elegans via JNK and p38 MAPK signalling pathways. Hence, we believed that arsenic and cadmium which are classified as metals without redox potential induced stress through p38 MAPK signalling pathways, but underlying stress pathways of P. nemipteri after the heavy metals exposure is not fully understood.…”
Section: Discussionmentioning
confidence: 99%